A Case Report of Tinea Capitis in Children: Utility of Trichoscopy - Harningtyas, Citra Dwi; Ervianti, Evy; Astari, Linda; Anggraeni, Sylvia; Yuri Widia (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Tinea capitis (TC) is the most prevalent pediatric superficial dermatophyte infection. Scalp dermoscopy or "trichoscopy” represents a valuable, noninvasive technique for the evaluation of patients with hair loss due to TC. Purpose: To characterize trichoscopic findings in children with clinical findings suggestive of TC. Case:  A 13-year-old boy was presented with a scaled plaque on his scalp that had appeared 1 month earlier. A physical examination revealed a scaly, nonerythematous, rounded lesion in the parietal area of the head. Wood's lamp yielded a blue fluorescence. Microscopic morphology from fungal culture found the typical spindle-shaped macroconidia of Microsporum canis. Trichoscopy showed mainly comma hair, corkscrew hair, morse code hair, bent hair, and zig zag hair. The patient was started on oral griseofulvin 20 mg/kg/day and antifungal shampoo for 8 weeks. The patient was cured after two months of treatment and trichoscopy returned to normal. Discussion: Fungal culture remains the gold standard in TC diagnosis, but it needs time. Trichoscopy can be an additional tool to help evaluate the diagnosis, aetiology, and follow up of this disorder. The presence of characteristic trichoscopic features (comma hairs, corkscrew hairs, Morse code-like hairs, zigzag hairs, bent hairs, block hairs, and i-hairs) is predictive of TC. The present analysis confirmed that trichoscopy is a useful method in differentiating between Microsporum and Trichophyton TC, which is important from the perspective of a different therapeutic approach. Conclusion: Trichoscopy is not only of value in the diagnosis of TC but also for the etiologic agent and follow-up after treatment in this case.